The Railroad - Kalman, Bobbie (New York : Crabtree Pub. Co., 1999)
Describes the development of the railroad in North America and its influence on the settling of the West during the nineteenth century.
Includes index.
8 - 11 years
Keywords: Railroads -- History -- Juvenile literature. -- 19th century -- United States; Railroads -- History. -- West (U.S.); United States -- Economic conditions -- 19th century